Phenotypic Divergence among Sweet Pepper Landraces Assessed by Agro-Morphological Characterization as a Biodiversity Source - Eva Martínez-Ispizua; Ángeles Calatayud; José Ignacio Marsal; Rubén Mateos-Fernández; María José Díez; Salvador Soler; José Vicente Valcárcel; Mary-Rus Martínez-Cuenca (Agronomy, 2022)
Traditional vegetable varieties constitute an important reservoir of biodiversity, so recovering, cultivating, and correctly classifying these landraces is part of key global heritage for the future of food security. In this study, 17 traditional pepper varieties from the Valencian Community (Spain) were characterized using 14 quantitative and 30 qualitative conventional morphological descriptors, including plant, flower, and fruit traits, in two ripening stages: green and red. As a result, landraces were grouped based mainly on their fruit morphology (G1: thin and elongated; G2: thick and robust; P-49: ball pepper). During a second trial, the preservation of the described characteristics was checked, and the number of fruit produced per plant was determined. From the acquired information, the most desirable traits that could be of interest for cultivation and harvesting practices were established, including erect growth habit, dense branching, big leaves, and uniformity and low persistence of fruit. Additionally, based mainly on fruit size and fruit wall thickness traits, the varieties with the highest potential to be marketed as fresh, P-37 (from G2), P-41, and P-72 (from G1), were determined. The ungrouped P-49 variety is an optimal candidate for industry processes because of its small size and robust fruit wall. The importance of phenotyping studies for preserving plant varieties is emphasized.